Aloe Medicinal Properties and Botanical Characteristics - Shuxratullayevna, Zebo Satibaldiyeva; qizi, Sadridinova FarangizAzizbek (American Journal of Biodiversity, 2025)
Aloe is one of the most widely used medicinal plants in traditional and modern healthcare systems due to its rich phytochemical composition and broad therapeutic effects. This paper outlines the key botanical characteristics of Aloe species, particularly Aloe vera, and highlights its major medicinal properties, including anti-inflammatory, antimicrobial, wound-healing, antioxidant, and gastrointestinal benefits. Special attention is given to its relevance in Uzbekistan, where interest in herbal medicine and local cultivation potential is increasing. Aloe-based natural remedies are commonly used in Uzbek households for skin care, burns, stomach discomfort, and immune strengthening. Expanding research and cultivation in Uzbekistan could enhance its application in pharmaceutical, cosmetic, and health industries.